1989
DOI: 10.1104/pp.89.4.1094
|View full text |Cite
|
Sign up to set email alerts
|

Development of Water Conducting Capacity in the Root Systems of Young Plants of Corn and Some Other C4 Grasses

Abstract: Development of the primary and early nodal roots was studied in Zea mays L., Zea mexlcana (Schrad.) Soil or sand sheaths encasing roots of grasses have been described as features found in desert and dry environments (13). More recently they have been described on corn (12) and mesophytic grasses in humid environments (3). Striking illustrations of such sheaths will be found in these three papers. The sheathed regions of corn roots coincide with the regions of immature xylem where LMX2 elements are still aliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 13 publications
2
23
0
1
Order By: Relevance
“…One result of this isolation from the transpiration tension is that immature roots may conserve water in young and older seedlings until an extensive root system is established. Wenzel et al (1989) showed that in corn no LMX is open in the roots of soil-grown seedlings up to as many as 14 d after germination and that plants of corn and three other C 4 grasses as large as that shown in Figure 1A have as little as 14% and rarely more than 50% of total root length with open LMX conducting tubes. Another result of the closed LMX may be that the meristematic tissues are protected from the transpiration tension.…”
Section: Delayed Development Of Xylemmentioning
confidence: 92%
“…One result of this isolation from the transpiration tension is that immature roots may conserve water in young and older seedlings until an extensive root system is established. Wenzel et al (1989) showed that in corn no LMX is open in the roots of soil-grown seedlings up to as many as 14 d after germination and that plants of corn and three other C 4 grasses as large as that shown in Figure 1A have as little as 14% and rarely more than 50% of total root length with open LMX conducting tubes. Another result of the closed LMX may be that the meristematic tissues are protected from the transpiration tension.…”
Section: Delayed Development Of Xylemmentioning
confidence: 92%
“…Ho\ve\er, recent studies in corn {Zea mays) ha\e shown that despite eotnplete ligtiificatioti, late tnetaxylem eletnents (ofteti very large) ha\ e dela> ed tnatitratioti with persistetit cross-walls atid protoplasm present up to 20-30 cm from the root tip (St Aubiti et al, 1986). Sitnilar finditigs were reported for teosinte {Zea mexicana), sorghum {Sorghntti bicolor) and sudati grass {Sorghu»i Sudanese) where all roots reached lengths of about 30 cm before the late metaxylem elements matured (Wenzel, McCully & Canny, 1989).…”
Section: N T H O D Ii C R I O Nmentioning
confidence: 99%
“…Water uptake along roots is related, for the radial pathway (water transport from soil to xylem vessels), to the differentiation of relatively impermeable structures (suberization) and for the axial pathway (water transport along roots), to xylem maturation [78]. In some monocot species, late metaxylem vessels (able to carry much of the water) were shown to open at large distances from the root tip (around 20-30 cm for main axes of maize [92]). Based on experimental data on water flow in maize roots [84] and architectural/ water transport modelling of the root system, Doussan et al [18,19] derived the variations of hydraulic conductance along maize primary and lateral roots, and showed the impact of these variations on the distribution of water uptake within the maize root system for the case of a uniform water avaiblity (Fig.…”
Section: Variations Along Rootsmentioning
confidence: 99%